es 2020
DOI: 10.20955/es.2020.31
|View full text |Cite
|
Sign up to set email alerts
|

Is the COVID-19 Pandemic a Supply or a Demand Shock?

Abstract: I n response to the COVID-19 outbreak, public health authorities around the world implemented mitigation measures such as social distancing, which shut down entire sectors of the economy, especially those that involve interpersonal contact, such as restaurants and salons. While authorities have forced many such establishments to close, leaving many workers jobless, and issued stay-at home orders (so-called lockdowns), consumers also decreased their use of these services. 1 Further, newly jobless workers reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 1 publication
0
42
0
5
Order By: Relevance
“…The intellectuals would come to a consensus with us that the global spread of corona pandemic has recently created spirals of systematic risks across markets in Asia. And, we can cite the role of supply, demand and financial shocks for such occurrences (Brinca et al, 2020). In order to control the adverse effects of these shocks, governments have responded with the conventional expansionary fiscal and monetary weapons along with other policy responses to protect their economies from plausible recessions.…”
Section: Methodsmentioning
confidence: 99%
“…The intellectuals would come to a consensus with us that the global spread of corona pandemic has recently created spirals of systematic risks across markets in Asia. And, we can cite the role of supply, demand and financial shocks for such occurrences (Brinca et al, 2020). In order to control the adverse effects of these shocks, governments have responded with the conventional expansionary fiscal and monetary weapons along with other policy responses to protect their economies from plausible recessions.…”
Section: Methodsmentioning
confidence: 99%
“…The result is a macro economic crisis comprised of simultaneous demand, supply, and financial shocks. Consumers are traveling less and purchasing fewer goods and services that bring them into close contact with others, global supply chains are disrupted, and financial service systems are facing liquidity strains (Brinca, Duarte, & e Castro, 2020;Triggs & Kharas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Economists may diverge in their views on how to best assess the COVID-19 variable, but many agree that it can be regarded as a hybrid supply-demand shock generating domino effect. Brinca, Duarte, and Faria-e-Castro explain this duplicity as a logical consequence of the spill-over effect [47]. They argue that at the supply end, the lockdown policy cost the working population their income and savings, causing them to initiate demand shock when they were forced to restrain from all non-essential purchases.…”
Section: Covid-19 As a Demand Shockmentioning
confidence: 99%
“…Although with high relevance, supply shock advocates draw conclusions less from evidence and more on inferences. Some of the more robust research evidence examining the supply shock was generated using econometric models [47]. On a more moderate note, Candia et al found that, as opposed to households that ultimately experience it as a supply disruption, only some companies perceive the crisis as a supply shock [60].…”
Section: Covid-19 As a Demand Shockmentioning
confidence: 99%